The amazing adventures of Bob Brown : a real-life zelig who wrote his way through the 20th century - Saper, Craig J. (Empire State Editions, 2016)
Biography of Robert Carlton ""Bob"" Brown, avant-garde publisher, poet and reading machine inventor, bestselling pulp fiction and Hollywood movie treatment writer, cookbook author with Cora and Rose Brown, advertiser copyrighter, editorial board member of the Masses, curator of A Museum of Social Change, and much more